IMMOBILIZATION DRIED MIX OF ALGAE FOR COPPER REMOVAL - & Alwared, Abdulkareem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to reveal the effectiveness of Immobilization of biomass (dried mix algae) in the form of bead for the removal of copper ions from synthetic polluted water. Various operational parameters such as pH (2–6), biosorbent dosage (0.5–20 g/L) and initial concentration (10–100 mg/L)The results concluded that  a removal efficiency reached up to 90 % , which indicated the fascinated and easiest the handling of biomass. Characterization of the immobilized algae was determined by the Scanning electron microscope with Energy Dispersive X-Ray Analysis (SEM- EDX). The result reveals that the equilibrium time can be reached within 60–80 min. Experimental data were compiled well with Langmuir and Freundlich isotherm with R2 = 0.97 and 0.93, respectively.